1993
DOI: 10.1128/jcm.31.11.3050-3052.1993
|View full text |Cite
|
Sign up to set email alerts
|

Growth in serum-free medium improves isolation of Chlamydia pneumoniae

Abstract: Infectivity titers were determined for eight Chlamydia pneumoniae strains simultaneously grown in serum-free and serum-supplemented cell culture media. Use of serum-free medium resulted in a 10to 50-fold increase in the susceptibility of HL cells to chlamydial infection. Comparative primary isolation of a wild-type strain also produced higher inclusion counts in a serum-free environment. Serum-free cultivation is recommended to increase the efficiency of C. pneumoniae isolation from clinical material and to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
1999
1999

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…The cell growth medium was Eagle's minimal essential medium with nonessential amino acids and 2 mM glutamine (EMEM) (GIBCO/BRL GmbH, Eggenstein, Germany), supplemented with 10% fetal calf serum (Biochrom KG, Berlin, Germany). Chlamydiae were continuously cultured as previously described (12,14,16,19) by centrifugation (2,000 x g at 35°C for 45 min) of infectious inocula onto host cell monolayers in multiwell tissue culture plates. Supernatants were replaced by the chlamydial isolation medium consisting of EMEM with 1 ,ug of cycloheximide (Sigma Chemical Co., St. Louis, Mo.)…”
mentioning
confidence: 99%
“…The cell growth medium was Eagle's minimal essential medium with nonessential amino acids and 2 mM glutamine (EMEM) (GIBCO/BRL GmbH, Eggenstein, Germany), supplemented with 10% fetal calf serum (Biochrom KG, Berlin, Germany). Chlamydiae were continuously cultured as previously described (12,14,16,19) by centrifugation (2,000 x g at 35°C for 45 min) of infectious inocula onto host cell monolayers in multiwell tissue culture plates. Supernatants were replaced by the chlamydial isolation medium consisting of EMEM with 1 ,ug of cycloheximide (Sigma Chemical Co., St. Louis, Mo.)…”
mentioning
confidence: 99%
“…Those values indicate markedly lower survival rates than were achieved in our study by the use of FCS-supplemented transport media. FCS apparently must not be omitted from transport media, although its use in the chlamydial isolation medium for cell culture is not obligatory (13). As in our study, a stabilizing effect of FCS during prolonged storage and a decreasing viability with elevated temperatures and extended holding periods have been noted by Theunissen et al (24), but some results in their investigation, such as the 100% retrieval reported to have occurred in SPG with 10% FCS after 48 h at 5 to 20ЊC, differ from those of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Host cells were grown in Eagle's minimal essential medium with nonessential amino acids and 2 mM glutamine (EMEM) (GIBCO/ BRL GmbH, Eggenstein, Germany), and 10% fetal calf serum (FCS) (Biochrom KG, Berlin, Germany). Chlamydiae were continuously cultured in an adaptation of recent protocols (13,14,18,26): briefly, infectious inocula of the stock strains were centrifuged at 2,000 ϫ g at 35ЊC for 45 min onto HEp-2 monolayers, and then supernatants were replaced by chlamydial isolation medium consisting of EMEM with 1 g of cycloheximide per ml (Sigma Chemical Co., St. Louis, Mo.). After 3 days of incubation at 35ЊC in 5% CO 2 , chlamydial growth was demonstrated by staining inclusions with a C. pneumoniae-specific mouse monoclonal antibody and fluorescein isothiocyanate-coupled secondary antibody according to the manufacturer's instructions (Cellabs Diagnostics Pty Ltd., Sydney, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study with asthma patients, an elevated IgG antibody level with a concomitant elevated IgA antibody level proved to be a useful marker of chronic C. pneumoniae infection (13). Unlike for Chlamydia trachomatis infections, culture and direct antigen detection with clinical specimens have proven to be unsuccessful in both acute and chronic C. pneumoniae infections (6,9,17,27). The PCR test is promising, but it is expensive and not yet available for routine analysis.…”
mentioning
confidence: 99%